The Method of Determining Clinical and Roentgenogrammetric Indicators of Hip Joint in Patients with Cerebral Palsy - Hoshko, V.Yu.; Naumenko, N.O.; Yatsuliak, M.B.; Cheverda, A.I.; Nemesh, M.M.; Martsyniak, S.M. (TERRA ORTHOPAEDICA, 2020)
Summary. There is no doubt that obtaining the true parameters of the hip joint makes it possible to determine the tactics of treatment of patients with cerebral palsy and it is a relevant object of studying. Objective: to improve the results of diagnostics of pathology of the hip joint in patients with cerebral palsy by developing our own method. Materials and Methods. The study included 20 patients (40 joints): 10 boys and 10 girls. Sixteen joints were operated on. The patients were 3-15 years of age. Femoral torsion according to Ruwe was clinically determined in all the patients; also, our own method for determining the clinical and roentgenogrammetric parameters of the hip joint (utility model patent No. 137567) was used. Results. Our own method is simple, available and cheap; it may be used in all medical institutions with X-ray rooms for the diagnosis of hip joint pathology, as well as for screening. Conclusions. Our own method is simple and reliable for determining the parameters of the hip joint in patients with cerebral palsy (femoral torsion, neck shaft angle, Wiberg’s angle, Reimer’s index, vertical migration index, acetabular angle, the angle of inclination of the acetabulum) in patients with cerebral palsy. Obtaining radiographic parameters of both hip joints after only one radiograph also significantly reduce the radiation load on the patient, since patients with cerebral palsy are the subject of screening throughout the entire period of their development. This method can be also applied during the examination and screening the patients with developmental disorders and other diseases of the hip joint.